Cognitive processes related to problematic pornography use (PPU): A systematic review of experimental studies. (June 2021) - Castro-Calvo, J.; Cervigón-Carrasco, V.; Ballester-Arnal, R.; Giménez-García, C.
Highlights: Some people experience symptoms derived from pornography viewing. Cognitive processes may be related to the development of Problematic Pornography Use (PPU). We performed a systematic review of 21 studies exploring cognitive processes related to PPU. We identified 4 cognitive processes relevant for the development and maintenance of PPU. Abstract: Introduction: Some people experience symptoms and negative outcomes derived from their persistent, excessive, and problematic engagement in pornography viewing (i.e., Problematic Pornography Use, PPU). Recent theoretical models have turned to different cognitive processes (e.g., inhibitory control, decision making, attentional bias, etc.) to explain the development and maintenance of PPU, but empirical evidence derived from experimental studies is still limited. In this context, the present systematic review aimed to review and compile the evidence around cognitive processes related to PPU. Methods: A systematic review was performed in accordance with PRISMA guidelines to compile evidence regarding cognitive processes related to PPU. We retained and analyzed 21 experimental studies addressing this topic. Results: Studies were focused on four cognitive processes: attentional bias, inhibitory control, working memory, and decision making. In brief, PPU is related to (a) attentional biases toward sexual stimuli, (b) deficient inhibitory control (in particular, to problems with motor response inhibition and to shift attention away from irrelevant stimuli), (c) worse performance in tasks assessing working memory, and (d) decision making impairments (in particular, to preferences for short-term small gains rather than long-term large gains, more impulsive choice patterns than non-erotica users, approach tendencies toward sexual stimuli, and inaccuracies when judging the probability and magnitude of potential outcomes under ambiguity). Conclusion: This systematic review offers a comprehensive overview of the current state of knowledge regarding the cognitive features related to PPU, and points out new areas that warrants further research.